Between Maternal Knowledge and Infant Compliance with Basic Immunization in the Sidomulyo Community Health Center Work Area in Bengkulu City 2025 - Rince Arifin; Emi Pebriani; Bella Anarkie (Student Scientific Journal, 2026)
According to the World Health Organization (WHO, 2023), immunization is a highly effective health intervention in reducing infant and toddler mortality. More than 1.8 million Indonesian children have not received complete routine immunizations over the past six years, from 2018 to 2023. This study aims to determine the relationship between maternal knowledge and compliance with basic immunizations in infants in the Sidomulyo Community Health Center (UPTD) Work Area, Bengkulu City, in 2025. The study used a cross-sectional design, with data collected by distributing questionnaires to 40 mothers with infants aged 12-59 months using a simple random sampling technique. Univariate analysis results showed that almost half of the respondents (17 (42.5%) in the Sidomulyo Community Health Center (UPTD) Work Area, Bengkulu City, had inadequate knowledge, and more than half (22 (55.0%) in the Sidomulyo Community Health Center (UPTD) Work Area, Bengkulu City, in 2025) were non-compliant with their infants' basic immunizations. Bivariate analysis revealed a significant relationship between maternal knowledge and infant compliance with basic immunizations in the Sidomulyo Community Health Center (Puskesmas) Work Area of Bengkulu City in 2025, with a p-value of 0.017. The Sidomulyo Community Health Center (Puskesmas) of Bengkulu City should enhance health promotion efforts through ongoing counseling and education regarding the importance of basic immunizations for infants. This education should not only emphasize the type and schedule of immunizations, but also the benefits, safety, and management of post-immunization side effects.